Characterization of a New Cyclohexylamine Oxidase From Acinetobacter sp. YT-02 - Zhou, Hui; Han, Zheng-gang; Fang, Ti; Chen, Yuan-yuan; Ning, Shang-bo; Gan, Ya-ting; Yan, Da-zhong (Frontiers in Microbiology, 2018)
Abstract Cyclohexylamine (CHAM) is widely used in various industries, but it is harmful to human beings and the environment. Acinetobacter sp. YT-02 can degrade CHAM via cyclohexanone as an intermediate. In this study, the cyclohexylamine oxidase (CHAO) gene from Acinetobacter sp. YT-02 was cloned. Amino acid sequence alignment indicated that CHAOYT-02 was 48% identical to its homolog from Brevibacterium oxydans IH-35A. The enzyme was expressed in Escherichia coli BL21 (DE3), and purified to apparent homogeneity by Ni-affinity chromatography. The purified enzyme was proposed to be a dimer of molecular mass of approximately 91 kDa. The enzyme exhibited its maximum activity at 50℃ and at pH 7.0. The enzyme was thermolabile as demonstrated by loss of its important percentage of activity after 30 min incubation at 50℃. Metal ions Mg2+, Co2+, and K+ had certain inhibitory effect on the enzyme activity. The kinetic parameters Km and Vmax were 0.252 ± 0.0180 mM and 4.30 ± 0.0833 M min−1, respectively. The biochemical properties, substrate specificities, and three-dimensional structures of CHAOYT-02 and CHAOIH-35 were compared.